Penerapan Metode TOPSIS untuk Seleksi Penerima Beasiswa (Studi Kasus: SMAN 2 Tebing Tinggi Timur) - Rahmalisa, Uci; Muhardi, Muhardi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
Government efforts to overcome the high cost of education by providing tuition assistance to underprivileged students in funding education, called scholarships. This scholarship is aimed at students who are economically disadvantaged. Students must have certain criteria that will be assessed by the school in considering their eligibility as scholarship recipients. Therefore, it is necessary to have a decision support system which will be able to shorten the selection time and improve quality in determining scholarship acceptance. the decision support system used is TOPSIS based on predetermined criteria. By using this method, it will be able to produce objective decisions in determining scholarship receipts at Tebing Tinggi Timur 2 High School.